Kasus Pencucian Uang Dalam Tinjauan Sistem Ekonomi Syari’ah - Sumadi Sumadi (Jurnal Ilmiah Ekonomi Islam, 2017)
Money laundering basically involves assets (income / wealth) that is disguised so that it can be used without being detected that the assets derived from illegal activities. Money laundering through income or assets derived from illegal activity is converted into financial assets that appear to come from legitimate sources. The purpose of this study was to determine how the viewpoint of the Islamic economic system against money laundering, how to solve the problem. This study used a qualitative approach using literature. Results of the study were achieved, in which money laundering is a crime that is so damaging to the country as well, because it can affect or damage the national economy, especially the financial stability of the country. It is completely contrary to the purpose tasyri 'which prevent hazards and create benefits. Money laundering damage, loss, danger, while distancing the benefit of human life, reprehensible, and forbidden that can be called as a crime and in the context of Islamic law. Money loundering view of Islamic law on this money is part immoral acts which leave the required command and does something which is forbidden, where the act was imposed. Thus, the sentence in this case is not determined by the size or the level is, means to determine the lower and upper bounds left entirely to the judge. How to cite: Sumadi, s. (2017). Kasus Pencucian Uang Dalam Tinjauan Sistem Ekonomi Syari’ah. Jurnal Ilmiah Ekonomi Islam, 3(03), 186-192. doi:http://dx.doi.org/10.29040/jiei.v3i03.131